Keindahan Rias Pengantin Paes Solo Basahan dalam Tradisi Pernikahan Jawa - Erna Setyowati; Rosiana Himmatus; Ratna Hidayati; Dinda Putri Nur N; Sherlita Puji Lestari; Sakti Putri Prasetya; Darul Falaqis Salaf (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The study purpose was to examine the aesthetic and symbolic meanings of Paes Solo Basahan bridal makeup in Javanese wedding traditions. This research aims to understand how each element of the makeup reflects cultural values and philosophies of married life. Materials and methods. This study used a qualitative descriptive approach. Data were collected through observation, interviews, and documentation, then analyzed to identify the meanings behind the makeup elements. Results. The findings show that elements such as paes, sanggul, dodotan, and accessories contain symbolic meanings related to purity, harmony, and wisdom. These elements represent hopes for a harmonious and prosperous married life. Conclusions. Paes Solo Basahan bridal makeup is not only an aesthetic element but also a cultural symbol that preserves Javanese values and identity.